Association of urinary vanin‐1 with kidney function decline in hypertensive patients. Issue 7 (24th May 2021) - Hosohata, Keiko; Matsuoka, Hiroyuki; Kumagai, Etsuko
Abstract: Previously, the authors reported the utility of urinary vanin‐1 as an early biomarker of kidney injury in spontaneously hypertensive rats and in humans. However, little is known about whether urinary vanin‐1 can be used to predict the clinical outcome. This study aimed to evaluate the predictive power of urinary vanin‐1 based on kidney function decline in hypertensive patients. The authors measured urinary vanin‐1 in 147 patients at the baseline and examined its association with the incidence of ≥20% decline in the estimated glomerular filtration rate (eGFR) using the Cox regression analysis. The mean age of the patients averaged 72.9 ± 8.2 years, and 39% were women. Median (interquartile range) urinary vanin‐1 was 0.33 (0–2.6) ng/mg Cr During a median follow‐up of 12 months, 14 patients showed kidney function decline. A higher urinary vanin‐1 level was associated with an increased risk of kidney function decline (hazard ratio, 9.87; 95% CI, 1.11–87.5) ( p  = .04) in the fully adjusted model. In conclusion, urinary vanin‐1 is an independent risk factor for kidney function decline in hypertensive patients and it could be useful in clinical settings. The underlying pathophysiologic mechanisms warrant additional investigation.